Physical Exercise−Mediated Changes in Redox Profile Contribute to Muscle Remodeling After Passive Hand-Rolled Cornhusk Cigarette Smoke Exposure - Thirupathi, Anand; Scarparo, Silvia; Silva, Paulo L.; Marqueze, Luis F.; Vasconcelos, Franciane T. F.; Nagashima, Seigo; Cunha, Eduardo B. B.; de Noronha, Lúcia; Silveira, Paulo C. L.; Nesi, Renata T.; Gu, Yaodong; Pinho, Ricardo A. (Frontiers in Physiology, 2020)
The consumption of different forms of cigarettes, especially handmade or natural cigarettes, which do not undergo industrial processing, has increased considerably worldwide. These cigarettes are erroneously considered healthier than industrialized cigarettes, but its toxicity induced health impacts are not well established. Physical exercise is one of the important strategies that prevent and treat smoking-related diseases, but the effects of various types of exercise on the muscles are still under investigation especially in the smoking exposure condition. Therefore, this study aimed to investigate the effects of combined physical (aerobic and resistance exercise) exercise on HRCC smoke-induced oxidative stress and further histoarchitecture alteration in the muscle. Male Swiss mice were exposed to ambient air or passively to the smoke of 12 cigarettes three times per day (four cigarettes per session) for 30 consecutive days with or without combined physical training. Forty-eight hours after the last training session, oxidative stress parameters, and total leukocyte count in bronchoalveolar lavage fluid (BALF) were measured. Further, quadriceps were removed for histological/immunohistochemical analysis. Combined physical training reverted the total leucocytes count in BALF, muscle fiber diameter, centralized core, and inflammatory markers in mice exposed to HRCC. In addition, increased Myf-5 and reduced TGF-β and nitrite levels were observed after physical training. However, there were no changes observed in SOD and GSH/GSSG ratio in HRCC-exposed mice after combined physical training. These results suggest that HRCC-induced alteration in the muscle redox profile and changes in the skeletal muscle structure, but combined physical training effectively contributed to muscle remodeling and muscle function without altering the muscle redox profile.